Split Course Hyperfractionated Accelerated Radio-Chemotherapy (SCHARC) for patients with advanced head and neck cancer: Influence of protocol deviations and hemoglobin on overall survival, a retrospective analysis - Stadler, Peter (BioMed Central, 2006)
BACKGROUND: The advantage of hyperfractionated accelerated radiation therapy for advanced head and neck cancer has been reported. Furthermore, randomized trials and meta-analyses have confirmed the survival benefit of additional chemotherapy to radiotherapy. We retrospectively analyzed the efficiency and toxicity of the Regensburg standard therapy protocol "SCHARC" and the overall survival of our patients. METHODS: From 1997 to 2004, 64 patients suffering from advanced head and neck cancer (88 % stage IV, 12 % stage III) were assigned to receive the SCHARC protocol. Around half of the patients were diagnosed with oro-hypopharynx carcinoma (52 %), one third with tongue and floor of mouth tumors (29 %) and one fifth (19 %) suffered from H & N cancer at other sites. The schedule consisted of one therapy block with 30 Gy in 20 fractions over a two week period with concomitant chemotherapy (d 1–5: 20 mg/m(2)/d DDP + 750–1000 mg/m(2)/d 5FU (cont. infusion). This therapy block was repeated after a fortnight break up to a cumulative dose of 60 Gy and followed by a boost up to 70 Gy (69–70.5 Gy). All patients assigned to this scheme were included in the survival evaluation. RESULTS: Forty patients (63 %) received both radiation and chemotherapy according to the protocol. The mean follow up was 2.3 years (829 d) and the median follow up was 1.9 years (678 d), respectively. The analysis of survival revealed an estimated 3 year overall survival rate of 57 %. No patient died of complications, 52 patients (80 %) had acute grade 2–3 mucositis, and 33 patients (58 %) suffered from acute grade 3 skin toxicity. Leucopenia was no major problem (mean nadir 3.4 g/nl, no patient < 1.0 g/nl) and the mean hemoglobin value decreased from 13.2 to 10.5 g/dl. Univariate analysis of survival showed a better outcome for patients with a hemoglobin nadir >10.5 g/dl and for patients who completed the protocol. CONCLUSION: The SCHARC protocol was effective in patients diagnosed with advanced head and neck cancer. It led to long-term disease control and survival in about 50 % of the patients with significant but acceptable toxicity. Most patients were not anemic at beginning of therapy. Therefore, we could assess the influence of pre-treatment hemoglobin on survival. However, a low hemoglobin nadir was associated with poor outcome. This result suggests an influence of anemia during therapy on prognosis.